2017
DOI: 10.1371/journal.pone.0187466
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial meningitis epidemiology and return of Neisseria meningitidis serogroup A cases in Burkina Faso in the five years following MenAfriVac mass vaccination campaign

Abstract: BackgroundHistorically, Neisseria meningitidis serogroup A (NmA) caused large meningitis epidemics in sub-Saharan Africa. In 2010, Burkina Faso became the first country to implement a national meningococcal serogroup A conjugate vaccine (MACV) campaign. We analyzed nationwide meningitis surveillance data from Burkina Faso for the 5 years following MACV introduction.MethodsWe examined Burkina Faso’s aggregate reporting and national laboratory-confirmed case-based meningitis surveillance data from 2011–2015. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 23 publications
1
51
0
1
Order By: Relevance
“…In Burkina Faso, meningitis accounts for 4% of all death representing the 7th most frequent cause of death . Only a quarter of suspected meningitis cases with CSF were laboratory‐confirmed as either S. pneumoniae , N. meningitidis, or H. influenza . Rapid and accurate diagnosis is mandatory for allowing prompt and appropriate care improving the clinical prognosis and minimizing debilitating sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Burkina Faso, meningitis accounts for 4% of all death representing the 7th most frequent cause of death . Only a quarter of suspected meningitis cases with CSF were laboratory‐confirmed as either S. pneumoniae , N. meningitidis, or H. influenza . Rapid and accurate diagnosis is mandatory for allowing prompt and appropriate care improving the clinical prognosis and minimizing debilitating sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…In countries located in the “meningitis belt” such as Burkina Faso, CSF samples are generally tested for the three main causative bacteria Neisseria meningitidis , Streptococcus pneumoniae , and Haemophilus influenzae by culture, antigen detection, and PCR . However, only about a quarter of suspected cases are laboratory‐confirmed with these tests . Little is known about the prevalence of HSV and MTB as agents responsible for severe but potentially curable aseptic meningoencephalitis in sub‐Saharan Africa .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we acknowledge that sufficient correlates of protection against MenA disease and carriage are not yet known. Some data are available from Burkina Faso showing a dramatic reduction of MenA disease incidence occurred after the introduction of a national MenA-TT vaccination campaign; however, more recent evidence showed an increase in MenA transmission, suggesting an increase in the number of susceptible people after years without routine vaccination against MenA disease or a catch-up campaign [73], allowing pathogen transmission to be reestablished in the general population as herd protection was diminished.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The reduction of the incidence of bacterial meningitis cases, epidemics and deaths following the introduction of MACV into meningtis belt was demonstrated [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Novak et al showed 71% decline in risk of meningitis (suspected cases) in Burkina Faso 1 year after the introduction of MACV [11].…”
Section: Introductionmentioning
confidence: 99%